Cell therapy worldwide: an incipient revolution. (March 2015) - Rao, Mahendra; Mason, Chris; Solomon, Susan
The regenerative medicine field is large, diverse and active worldwide. A variety of different organizational and product models have been successful, and pioneering entrepreneurs have shown both what can work and, critically, what does not. Evolving regulations, novel funding mechanisms combined with new technological breakthroughs are keeping the field in a state of flux. The field struggles to cope with the lack of infrastructure and investment, it nevertheless has evolved from its roots in human stem cell therapy and tissue and organ transplants to a field composed of a variety of products from multiple cell sources with approval for use in numerous countries. Currently, tens of thousands of patients have been treated with some kind of cell therapy.